Vigorous Root Growth Is a Better Indicator of Early Nutrient Uptake than Root Hair Traits in Spring Wheat Grown under Low Fertility - Wang, Yaosheng; Thorup-Kristensen, Kristian; Jensen, Lars Stoumann; Magid, Jakob (Frontiers in Plant Science, 2016)
A number of root and root hair traits have been proposed as important for nutrient acquisition. However, there is still a need for knowledge on which traits are most important in determining macro- and micronutrient uptake at low soil fertility. This study investigated the variations in root growth vigour and root hair length and density among spring wheat genotypes and their relationship to nutrient concentrations and uptake during early growth. Six spring wheat genotypes were grown in a soil with low nutrient availability. The root and root hair traits as well as the concentration and content of macro- and micronutrients were identified. A significant genetic variability in root and root hair traits as well as nutrient uptake was found. Fast and early root proliferation and long and dense root hairs enhanced uptake of macro- and micronutrients under low soil nutrient availability. Vigorous root growth, however, was a better indicator of early nutrient acquisition than root hair length and density. Vigorous root growth and long and dense root hairs ensured efficient acquisition of macro- and micronutrients during early growth and a high root length to shoot dry matter ratio favoured high macronutrient concentrations in the shoots, which is assumed to be important for later plant development.